2021
DOI: 10.1111/jcal.12614
|View full text |Cite
|
Sign up to set email alerts
|

Virtual academic conferences as learning spaces: Factors associated with the perceived value of purely virtual conferences

Abstract: Background: The COVID-19 outbreak came with an unprecedented opportunity to investigate how the new reality of social distancing and limited international travel will affect the organization of academic conferences.Objectives: Drawing on conceptualization of academic conferences as professional learning spaces, in this study, we examine the factors associated with the perceived value of purely virtual academic conferences and how such perceptions differ between participants from different research fields. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Some respondents felt that online ISCs were a poor substitute for the real thing, but to some extent they filled the lack of coming together. This coincides with Seidenberg et al (2021) who stated that when physical gatherings are not possible, online conferences provide a learning space for researchers. Researchers may discuss their findings with colleagues and present their work without meeting in-person, and they have a possibility to publish in the post-conference journal or proceedings.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Some respondents felt that online ISCs were a poor substitute for the real thing, but to some extent they filled the lack of coming together. This coincides with Seidenberg et al (2021) who stated that when physical gatherings are not possible, online conferences provide a learning space for researchers. Researchers may discuss their findings with colleagues and present their work without meeting in-person, and they have a possibility to publish in the post-conference journal or proceedings.…”
supporting
confidence: 82%
“…Because of the pandemic, conference organizers of in-person conferences were faced with three choices: to cancel the conference, to postpone, or to use online solutions. Seidenberg et al (2021) attempted to understand how the new reality of social distancing and limited international travel affected academic conferences. When physical gatherings are not possible, online conferences provide a learning space for researchers.…”
Section: Conceptual Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive encounters can stimulate a positive social response such as brainstorming or networking with colleagues at an in-person academic conference (Oester et al, 2017). The study by Seidenberg et al (2021) found that 80% of virtual conference participants ranked the importance of social interaction as high or very high. The study by Yu et al (2020) also found that virtual conference attendees derive pleasure from making connections with people knowledgeable in the discipline while also reducing their environmental footprint.…”
Section: Relatednessmentioning
confidence: 99%
“…Prior to 2020, virtual academic conferences were scarce (Seidenberg et al, 2021). However, the proliferation of virtual conferences continues in 2021 with the anticipation that large group in-person gatherings will eventually be permitted without restrictions.…”
mentioning
confidence: 99%